AT1‐AA Is Produced in Offspring in Response to Placental Ischemia and Is Lowered by B‐Cell Depletion Without Compromising Overall Offspring Health - Nathan Campbell; Evangeline Deer; Dylan Solise; Denise C. Cornelius; Ty Turner; Lorena M. Amaral; Owen Herrock; Ariel Jordan; Shivani Shukla; Tarek Ibrahim; Babbette LaMarca (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Preeclampsia, new‐onset hypertension during pregnancy alongside other organ dysfunction, is the leading cause of mortality for the mother and low birth weight for the baby. Low birth weight contributes to high risk of cardiovascular disorders later in life. Women with preeclampsia have activated B cells producing agonistic autoantibodies to AT1‐AA (angiotensin II type I receptor). We hypothesize that rituximab, a B cell‐depleting chemotherapeutic, will deplete maternal B cells in reduced uterine perfusion pressure (RUPP) rats without worsening the effect of placental ischemia on pup growth and survival. Methods and Results To test this hypothesis, the RUPP procedure was performed, and rituximab was continuously infused via miniosmotic pump. Maternal blood and tissues were collected. A separate group of dams were allowed to deliver, pup weights were recorded, and at 4 months of age, tissues were collected from offspring. Immune cells were measured via flow cytometry, and AT1‐AA was quantified using a contraction bioassay. Blood pressure increased in RUPP rats and was normalized with rituximab treatment. RUPP offspring also had increased circulating B cells, cytolytic natural killer cells, and increased circulating AT1‐AA, which were normalized with maternal rituximab treatment. This is the first study to analyze the AT1‐AA in RUPP offspring, which was normalized with rituximab. Conclusions Our findings indicate that perinatal rituximab lowers maternal mean arterial pressure in RUPP rats and improves birth weight, circulating AT1‐AA, and circulating natural killer cells, indicating that rituximab improves adverse fetal outcomes in response to placental ischemia.